Not-sew-wicked stepmom. 7 - Iru (Graphic novelist); Mo9Rang (Graphic novel illustrator) (Ize Press, 2025)
The king of Nerghen has been hugging everyone he meets--everyone except his wife, that is! Not sure what to make of Sabrian's odd behavior, Abigail can't help but wonder why he seems to be avoiding her...To complicate matters further, Abigail's brother, Prince Kane Kronenberg, arrives for a visit. What initially seems like a touching reunion between siblings takes a turn when his treatment of her dredges up some nauseating memories from Abigail's past life. Dealing with a brother she can hardly remember is difficult enough, but with her husband keeping his distance and her self-loathing threatening to consume her, will Abigail manage to keep her wits about her and make it through Kane's stay?--